1988
DOI: 10.1095/biolreprod39.4.758
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism and Control of Rabbit Oviduct Fluid Formation1

Abstract: The formation of rabbit oviduct fluid was monitored continuously by using an in situ vascular perfusion technique. Oviduct fluid was secreted linearly for at least 3 h at a mean rate of 20.8 +/- 1.5 microliter/h in estrous does. The rate more than doubled on Day 1 following mating, was similar to the value at estrus on Day 2, and dropped to 8.3 microliter on Day 3. Dibutyryl cyclic adenosine 3',5'-monophosphate (cAMP, 1 mM) added to the vascular medium abolished fluid secretion. The same response was obtained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Oviductal viscosity varies during the estrus cycle. Around ovulation, ciliated cells in the isthmus epithelium are covered by a dense, tenacious mucous that disappears after ovulation [14]; estrogen-regulated secretion of oviductal fluid increases 2-3 fold at estrus [15]. Fluid viscosity also affects sperm movement – as viscosity increases, sperm flagella propagation velocity, wave amplitude, and energy expenditure decrease [16].…”
Section: Introductionmentioning
confidence: 99%
“…Oviductal viscosity varies during the estrus cycle. Around ovulation, ciliated cells in the isthmus epithelium are covered by a dense, tenacious mucous that disappears after ovulation [14]; estrogen-regulated secretion of oviductal fluid increases 2-3 fold at estrus [15]. Fluid viscosity also affects sperm movement – as viscosity increases, sperm flagella propagation velocity, wave amplitude, and energy expenditure decrease [16].…”
Section: Introductionmentioning
confidence: 99%
“…These criteria are satisfied by the technique of vascular perfusion, which has been applied to the rabbit oviduct (Leese and Gray, 1985;Gott et al, 1988;Dickens and Leese, 1994). We now report the application of this method to the human Fallopian tube, together with an analysis of the tubal fluid formed for three nutrients, glucose, pyruvate and lactate, which are important in early human embryo metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…Water follows the ion movements towards the osmotic equilibrium and thus accumulates in the lumen [29]. Movements of chloride ions from basal to apical have been observed in the epithelium of the oviduct consistent with it being a chloride secretory epithelium [2,4,26,30]. In vascularly perfused rabbit oviduct, inhibition of chloride ion transport decreased vascular to lumen Cl Ϫ flux and the rate of fluid secretion [3].…”
Section: Discussionmentioning
confidence: 91%
“…Using a vascular perfusion technique, Gott et al [2] and Dickens and Leese [3] found that basal to apical movements of chloride ions were associated with tubal fluid secretion in the rabbit oviduct. These chloride fluxes were sensitive to blockade of Cl Ϫ /HCO 3 Ϫ exchange and Na ϩ /K ϩ / 2Cl Ϫ cotransport [2], which is consistent with the oviduct being a Cl Ϫ secretory epithelium as is found in other tissues such as the kidney proximal tubule and the airways. Dickens et al [4] then grew rabbit oviduct epithelial cells as a polarized layer in primary culture.…”
Section: Introductionmentioning
confidence: 99%